Hudkänsla - Sturesson Witt, Linda (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2004)
Pimples can, when they appear, claim much more space in life than just the spots in the face. For the one who is badly affected, pimples become central for the way in which the person acts, feels and experiences the world. The many hours in front of the mirror is a socialisation into a stigmatised identity where the critical gaze of others and a feeling of shame are constantly present. The affected ones go to any length to take control over body, skin, face and looks. If different cures or heavy makeup is not enough, all kinds of body micro-practices are set to work: using one's hair or hands to cover up or avoiding bright lights. As an acne person one experiences the world through the pimples, sensitizing oneself to situations, norms and the cultural interpretations of others.